2020
DOI: 10.1002/admi.202000185
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoelectrochemical Performance by Interface Engineering in Ternary g‐C3N4/TiO2/PbTiO3 Films

Abstract: Ferroelectric materials recently rise as promising candidates in solar energy harvesting owing to their unconventional photophysics, such as above-bandgap photovoltage, [6] tunable photovoltaic outputs, and birefractive behaviors. [7] These unique properties stem from the centrosymmetry breaking and spontaneous polarization of ferroelectrics, which produces an internal field that drives the efficient separation of photocarriers. [8] PbTiO 3 (PTO), as a prototypical ferroelectric perovskite oxide, stands out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Open ). This phase, which has often been observed both in Bi 4 Ti 3 O 12 powder samples and films [52][53][54][55][56][57][58][59][60][61][62][63][64] depending on synthesis temperature, Bi:Ti molar ratio, substrate, and film growth condition, has been proven to decompose at temperatures higher than 600°C ( †ESI, Figure S1), in accordance with the literature. 65 However, such heating conditions cannot be employed in the fabrication of the BiTO layers due to the use of FTO-coated glass substrates ( †ESI, section S1).…”
Section: Sustainable Energy and Fuels Accepted Manuscriptsupporting
confidence: 83%
See 1 more Smart Citation
“…Open ). This phase, which has often been observed both in Bi 4 Ti 3 O 12 powder samples and films [52][53][54][55][56][57][58][59][60][61][62][63][64] depending on synthesis temperature, Bi:Ti molar ratio, substrate, and film growth condition, has been proven to decompose at temperatures higher than 600°C ( †ESI, Figure S1), in accordance with the literature. 65 However, such heating conditions cannot be employed in the fabrication of the BiTO layers due to the use of FTO-coated glass substrates ( †ESI, section S1).…”
Section: Sustainable Energy and Fuels Accepted Manuscriptsupporting
confidence: 83%
“…A lot of work has been published on the study and development of poled ferroelectric photoelectrodes such as BiFeO 3 , [31][32][33][34][35][36][37][38][39][40] BaTiO 3 , [41][42][43][44][45] Li/Na/K-NbO 3 , [45][46][47][48][49] PbTiO 3 -PbZrTiO 3 , [50][51][52][53] and SrTiO 3 , 54,55 for the PEC water-splitting reaction, but the use of ferroelectric photocathodes for CO 2 PEC reduction has not been exploited yet. On the other hand, some studies on the production of BiTO ferroelectric layers have been reported for photovoltaic applications, [56][57][58] and only one preliminary work on photo-electrocatalysis has been reported, where thin lm BiOI/BiTO electrodes were fabricated via a metering rod method for the photo-electrochemical characterization of this heterostructure, as a photoanode in the ferroelectric-assisted water-splitting reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The principle of photoelectron chemistry operates by following conventional solid-state photodetectors’ typical carrier generation, separation, and migration processes. However, it also involves a distinctive electrochemical process, which includes ion diffusion processes at the semiconductor–electrolyte interface and redox reactions in solution. Importantly, the polarity of the photocurrent in a PEC device can be altered by changing the wavelength of the incident light or the applied bias potential, a phenomenon referred to as PEC photocurrent switching (PEPS). This modulation is achieved by artificially controlling the carrier migration and transport processes within PEC devices, resulting in a positive or negative photocurrent direction. This forms the foundation for utilizing PEC devices in logic gates, photo convulsions, and other information devices. , …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the metal-free polymer graphitic carbon nitride (g-C 3 N 4 ) has been intensively studied for photocatalytic water splitting due to its appropriate band gap, high chemical stability [11], visible light response, high earth abundance, and non-toxic elements [12][13][14]. However, pristine g-C 3 N 4 has been rarely reported as photoelectrode due to its poor electron and hole conductivity and low quantum efficiency (IPCE) [15,16]. Great efforts have been made to improve the performance of pristine g-C 3 N 4 by developing new composite electrode materials.…”
Section: Introductionmentioning
confidence: 99%